Heat treatment process for improving high-temperature durability of GH2909 alloy

Through a new heat treatment process, including one-solid solution treatment, stabilizing heat treatment and one-time aging treatment, the problems of poor high-temperature durability and complex process of GH2909 alloy are solved, and the high-temperature durability and plasticity of the alloy are synergistically improved, and the process is simplified and cost is reduced.

CN119800257AActive Publication Date: 2025-04-11UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411927677.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In the prior art, the high-temperature durability of GH2909 alloy has poor high-temperature durability, complex process, long process, strength and plasticity cannot be improved synergistically, and the plasticity changes are irregular.

Method used

A heat treatment process for improving the high-temperature and long-lasting performance of GH2909 alloy is proposed, including surface pretreatment, one solid solution treatment, stabilization heat treatment and one aging treatment, replacing the traditional two solid solution and two aging or preparatory heat treatment + two-stage solid solution treatment process.

Benefits of technology

Through this process, the process flow is shortened, the cost is reduced, and the efficiency is improved. The high-temperature longevity life of the alloy can reach more than 90 hours, which is more than 40% higher than the traditional process, while improving the plasticity and high-temperature long-lasting performance of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800257A_ABST
    Figure CN119800257A_ABST
Patent Text Reader

Abstract

The invention provides a heat treatment process for improving the high-temperature durability of a GH2909 alloy, and relates to the technical field of high-temperature alloy heat treatment. The method comprises the steps that the surface of an alloy part is pretreated, and the alloy part with the clean surface is obtained; carrying out primary solution treatment, and carrying out air cooling to room temperature; then carrying out high-temperature pretreatment, and carrying out air cooling to room temperature; and finally, the alloy part is subjected to primary aging treatment, and the high-temperature durability is improved after air cooling. The GH2909 alloy is subjected to uniquely-designed efficient heat treatment through one-time solution treatment, stabilizing treatment and one-time aging treatment, so that the plasticity and the high-temperature durability of the alloy are synergistically improved; the method is simple and easy to operate, green and environment-friendly, low in cost, short in process, high in efficiency and beneficial to industrial large-scale production and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment of high-temperature alloys, and in particular to a heat treatment process for improving the high-temperature durability of a GH2909 alloy. Background Art

[0002] High-temperature alloys are a type of metal material developed based on the needs of aviation jet engines. They can withstand complex stresses under high-temperature oxidation and gas corrosion conditions of 600-1200°C and can achieve long-term stable service. High-temperature alloys are mainly used to manufacture hot end components of aviation engines and gas turbines. They are also important materials for aerospace rocket engines, energy, and chemical industries. In the prior art, high-temperature alloys can generally be divided into three categories according to the type of matrix elements: nickel-based, cobalt-based, and iron-based high-temperature alloys, among which nickel-based alloys are the most widely used.

[0003] GH2909 alloy is a γ′ phase precipitation-strengthened high-temperature alloy. The microstructure after heat treatment is composed of γ solid solution, γ′ phase, Laves phase and ε phase. The strength of the alloy mainly comes from the number and size of the γ′ phase precipitation phase. Generally, it requires one solution treatment + two aging treatments, or two solution treatments + two aging treatments to obtain an alloy material with improved room temperature strength and stability. However, these methods consume a lot of heat energy, the preparation process is relatively long, and the strength and plasticity cannot be well improved.

[0004] For example: Chinese patent CN114277232A discloses a method and device for improving the strength of GH2909 alloy forgings. The heat treatment method is two solution treatments + two aging treatments. The total treatment time is at least about 18 hours without calculating the time for raising and lowering the temperature. The treatment cycle is long and the cost is high. The strength of the obtained material is low, and the plasticity is reduced or increased, and the change pattern is difficult to predict.

[0005] Chinese patent CN114807796A discloses a heat treatment process for improving the high temperature plasticity of GH2909 alloy. The heat treatment method is preliminary heat treatment + two-stage solid solution treatment. The total treatment time is at least about 18 hours without calculating the time for raising and lowering the temperature. Although the two-stage solid solution treatment can improve the high temperature plasticity of the alloy, not only the preparation process is time-consuming, but also the cooling speed is fast, and the effect of improving the plasticity is not good. Summary of the invention

[0006] In order to solve the technical problems in the prior art of poor high temperature durability of GH2909 alloy, complex two-step aging process, complex two-step aging treatment process, complex two-solution treatment + two-aging treatment process, complex preliminary heat treatment + two-stage solution treatment process, long process time, inability to improve strength and plasticity synergistically, irregular plasticity change law, etc.: the present invention proposes a heat treatment process for improving the high temperature durability of GH2909 alloy that can solve the above problems, and the technical solution is as follows:

[0007] A heat treatment process for improving the high temperature and durability performance of a GH2909 alloy, the heat treatment process for improving the high temperature and durability performance of a GH2909 alloy comprises the following steps:

[0008] S1. Surface pretreatment: pretreating the surface of the GH2909 alloy component to obtain a GH2909 alloy component with a clean surface;

[0009] S2, primary solution treatment: subjecting the GH2909 alloy component whose surface is cleaned in S1 to a primary solution treatment, and air cooling it to room temperature to obtain a GH2909 alloy component after the solution treatment;

[0010] S3, stabilization heat treatment: high temperature pretreatment is performed on the GH2909 alloy component after S2 solid solution treatment, and air cooling is performed to room temperature to obtain a GH2909 alloy component after stabilization treatment;

[0011] S4. Primary aging treatment: Perform primary aging treatment on the GH2909 alloy parts after S3 stabilization heat treatment, air cool to room temperature, and obtain GH2909 alloy with improved high temperature endurance performance.

[0012] Optionally, the GH2909 alloy in S1 is in the shape of a rod with a size of Φ170mm, φ220mm, Φ300mm, and is treated in a standard long-time double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC); the room temperature tensile strength is 1300-1330MPa, with a standard deviation of 15-27MPa; the room temperature yield strength is 965-1020MPa, with a standard deviation of 19-35MPa; the room temperature elongation is 14.7-18.2%, with a standard deviation of 0.7-2.1%; the room temperature cross-sectional shrinkage is 27-35%, with a standard deviation of 2.7-5.9%; the room temperature hardness is 370-380HB, with a standard deviation of 2-7HB; the high temperature tensile strength of 650℃ is 975-101 0MPa, standard deviation is 15-25MPa; the yield strength at 650℃ high temperature is 827-870MPa, standard deviation is 20-37MPa; the elongation at 650℃ high temperature is 15.5-17.4%, standard deviation is 3.8-7.3%; the cross-sectional shrinkage at 650℃ high temperature is 28.0-43.5%, standard deviation is 6.7-11.9%; the endurance life under 650℃ high temperature and 510MPa stress conditions is 57.7-67.4h, standard deviation is 2.7-7.6h; the elongation after fracture under 650℃ high temperature and 510MPa stress conditions is 12.4-20.8%, standard deviation is 5.1-10.4%; the cross-sectional shrinkage under 650℃ high temperature and 510MPa stress conditions is 29-41%, standard deviation is 4.7-6.9%.

[0013] Optionally, the shape of the GH2909 alloy in S1 is annular, with dimensions of 500-600mm in outer diameter, 400-500mm in inner diameter, 70-100mm in height, chord sampling, and the treatment state is standard long-term double aging treatment 1 (720°C×(8±0.5)h / FC→620°C×(8±0.5)h / AC); the tensile strength at room temperature is 1300-1340MPa, with a standard deviation of 15-27MPa; the yield strength at room temperature is 955-1031MPa, with a standard deviation of 20-37MPa; the elongation at room temperature is 15.0-20.2%, with a standard deviation of 0.7-2.3%; the cross-sectional shrinkage at room temperature is 27-38%, with a standard deviation of 3.2-4.8%; the hardness at room temperature is 365-380HB, with a standard deviation of 2-8HB; the high temperature resistance of 650°C is 1000-11000MPa, with a standard deviation of 10-2000MPa; the room temperature resistance ... The tensile strength is 985-1015MPa, and the standard deviation is 16-19MPa; the yield strength at a high temperature of 650℃ is 837-875MPa, and the standard deviation is 25-37MPa; the elongation at a high temperature of 650℃ is 17.5-20.4%, and the standard deviation is 3.8-6.5%; the cross-sectional shrinkage at a high temperature of 650℃ is 27.0-44.5%, and the standard deviation is 6.7-10.7%; the endurance life under the conditions of a high temperature of 650℃ and a stress of 510MPa is 60-65.4h, and the standard deviation is 2.7-4.6h; the elongation after fracture under the conditions of a high temperature of 650℃ and a stress of 510MPa is 14.4-21.8%, and the standard deviation is 5.1-7.8%; the cross-sectional shrinkage under the conditions of a high temperature of 650℃ and a stress of 510MPa is 31-43%, and the standard deviation is 4.7-5.7%.

[0014] Optionally, the shape of the GH2909 alloy in S1 is a square billet with an outer diameter of 100mm×100mm×100mm, and the treatment state is standard long-term double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC); the room temperature tensile strength is 1310-1345MPa, and the standard deviation is 14-20MPa; the room temperature yield strength is 970-1040MPa, and the standard deviation is 20-40MPa; the room temperature elongation is 15.5-19.2%, and the standard deviation is 0.6-2.4%; the room temperature cross-sectional shrinkage is 26-35%, and the standard deviation is 2.4-4.3%; the room temperature hardness is 375-385HB, and the standard deviation is 3-7HB; the high temperature tensile strength of 650℃ is 980-10 20MPa, standard deviation is 10-18MPa; the yield strength at 650℃ high temperature is 848-877MPa, standard deviation is 25-29MPa; the elongation at 650℃ high temperature is 16.5-21.4%, standard deviation is 3.8-7.1%; the cross-sectional shrinkage at 650℃ high temperature is 27.1-41.8%, standard deviation is 6.7-9.7%; the endurance life under 650℃ high temperature and 510MPa stress conditions is 58.0-66.7h, standard deviation is 1.9-4.1h; the elongation after fracture under 650℃ high temperature and 510MPa stress conditions is 15.1-19.8%, standard deviation is 2.7-6.7%; the cross-sectional shrinkage under 650℃ high temperature and 510MPa stress conditions is 29-42%, standard deviation is 4.8-6.2%.

[0015] Optionally, the temperature of the first solution treatment in S2 is 970-1010°C, and the holding time is 60-70min: then air-cooled to room temperature at a rate of 50-80°C / min.

[0016] Optionally, the temperature of the stabilization treatment in S3 is 810-840°C, and the holding time is 30-50min: then air-cooled to room temperature at a rate of 50-80°C / min.

[0017] Optionally, the temperature of the primary aging treatment in S4 is 640-660°C, and the holding time is 6-8h: then air-cooled to room temperature at a rate of 50-80°C / min.

[0018] Optionally, the GH2909 alloy in S3 is in the shape of a rod with a size of Φ170mm, Φ220mm, Φ300mm, and is subjected to a solid solution treatment + a stabilization treatment + an aging treatment; the room temperature tensile strength is 1350-1380MPa, with a standard deviation of 10-17MPa; the room temperature yield strength is 1020-1050MPa, with a standard deviation of 9-14MPa; the room temperature elongation is 17.9-23.2%, with a standard deviation of 0.8-1.7%; the room temperature cross-sectional shrinkage is 27-39%, with a standard deviation of 2.9-4.8%; the room temperature hardness is 370-385HB, with a standard deviation of 3-8HB; the high temperature tensile strength of 650°C is 1005-1025MPa, with a standard deviation of 12-26 MPa; the yield strength at 650℃ is 850-870MPa, with a standard deviation of 14-27MPa; the elongation at 650℃ is 11.5-21.4%, with a standard deviation of 2.3-5.7%; the cross-sectional shrinkage at 650℃ is 35.0-44.5%, with a standard deviation of 2.7-4.9%; the endurance life at 650℃ and 510MPa stress is 90.4-105.1h, with a standard deviation of 2.1-3.4h; the elongation at break at 650℃ and 510MPa stress is 17.1-22.7%, with a standard deviation of 2.7-5.1%; the cross-sectional shrinkage at 650℃ and 510MPa stress is 37.0-47.5%, with a standard deviation of 2.5-5.2%.

[0019] Optionally, the shape of the GH2909 alloy in S3 is annular, with dimensions of 500-600mm in outer diameter, 400-500mm in inner diameter, 70-100mm in height, chord sampling, and after one solution treatment + stabilization treatment + one aging treatment; the room temperature tensile strength is 1340-1370MPa, with a standard deviation of 11-15MPa; the room temperature yield strength is 1025-1060MPa, with a standard deviation of 10-14MPa; the room temperature elongation is 18.8-24.5%, with a standard deviation of 0.7-1.4%; the room temperature cross-sectional shrinkage is 30-39%, with a standard deviation of 2.7-4.2%; the room temperature hardness is 370-385HB, with a standard deviation of 3-9HB; the high temperature tensile strength of 650°C is 1000-1020MPa , standard deviation is 12-20MPa; the yield strength at 650℃ high temperature is 830-870MPa, standard deviation is 20-30MPa; the elongation at 650℃ high temperature is 11.5-20.4%, standard deviation is 3.7-5.1%; the cross-sectional shrinkage at 650℃ high temperature is 35.0-41.5%, standard deviation is 2.7-3.8%; the endurance life under 650℃ high temperature and 510MPa stress conditions is 98.4-120.1h, standard deviation is 4.1-6.4h; the elongation after fracture under 650℃ high temperature and 510MPa stress conditions is 18.2-28.7%, standard deviation is 2.2-5.0%; the cross-sectional shrinkage under 650℃ high temperature and 510MPa stress conditions is 38.0-48.0%, standard deviation is 2.3-6.2%.

[0020] Optionally, the shape of the GH2909 alloy in S3 is a square billet with an outer diameter of 100mm×100mm×100mm, and after a solid solution treatment + stabilization treatment + an aging treatment; the room temperature tensile strength is 1200-1230MPa, and the standard deviation is 15-28MPa; the room temperature yield strength is 890-945MPa, and the standard deviation is 19-35MPa; the room temperature elongation is 14.7-18.2%, and the standard deviation is 0.7-2.1%; the room temperature cross-sectional shrinkage is 26-37%, and the standard deviation is 2.7-5.9%; the room temperature hardness is 360-365HB, and the standard deviation is 2-7HB; the high temperature tensile strength of 650°C is 935-980MPa, and the standard deviation is 15-25MPa ; The yield strength at 650℃ is 784-820MPa, with a standard deviation of 20-40MPa; the elongation at 650℃ is 15.5-29.4%, with a standard deviation of 3.8-9.3%; the cross-sectional shrinkage at 650℃ is 27.0-47.5%, with a standard deviation of 6.7-11.9%; the endurance life at 650℃ and 510MPa stress is 95.4-111.2h, with a standard deviation of 5.1-6.8h; the elongation at break at 650℃ and 510MPa stress is 17.5-24.7%, with a standard deviation of 2.2-4.8%; the cross-sectional shrinkage at 650℃ and 510MPa stress is 36.2-47.1%, with a standard deviation of 2.2-6.9%.

[0021] Optionally, the microstructure of the GH2909 alloy component after vacuum brazing + primary aging is composed of 73.95-77.45% of γ solid solution, 14.71-15.43% of γ′ phase, 4.06-5.36% of Laves phase, 1.21-1.89% of ε phase and 2.57-3.37% of G phase; (γ solid solution is generally not studied, and the shape and size are not fixed (Determined) Among them, the shape of the γ′ phase is small spherical or cubic, with an average size of 18.84-19.72nm; the shape of the Laves phase is spherical or short rod-shaped, with an average major axis length of 1.45-1.84μm and an average minor axis length of 0.75-0.86μm; the shape of the ε phase is needle-shaped, with an average length of 0.89-1.61μm; the shape of the G phase is blocky or short rod-shaped, with an average size of 0.91-1.24μm.

[0022] Technical principle of the present invention:

[0023] The heat treatment process of the present invention does not focus on the heating rate and cooling rate of the treatment process. The selection of the heating rate is to ensure the normal use of the heating furnace, and a lower heating power is selected, which is about 10-30°C / min; the selection of the cooling rate is in the form of air cooling. Since the air cooling rate is a numerical range and the specific value cannot be selected artificially, the value is only an empirical value determined according to the size of the alloy component; the focus of the present invention is on the selection of the temperature and holding time of the stabilization treatment and the primary aging treatment: the temperature of the stabilization treatment is 810-840°C. According to the CCT curve of the alloy precipitation phase, the precipitation temperature range of the ε phase is between 700-900°C, and the precipitation temperature of the G phase is between 680-850°C. The temperature close to the peak precipitation temperature of the G phase is selected as the stabilization treatment temperature; the holding time is selected to be 30-50min. According to the alloy CCT curve, although the precipitation temperatures of the ε phase and the G phase overlap, the precipitation kinetics of the ε phase are slow, and it takes about 1h to precipitate, while the G phase precipitates before the ε phase precipitates. The temperature of the primary aging treatment is 640-660℃, and the holding time is 6-8h. According to the alloy CCT curve, the precipitation temperature of the main strengthening phase γ′ phase of the alloy is 600-720℃. Selecting a lower temperature close to the precipitation limit for aging can ensure that the dense precipitation of the γ′ phase reaches near saturation, and at the same time, it will not grow excessively, ensuring the stability of the alloy strength.

[0024] Compared with the prior art, the above technical solution has at least the following beneficial effects:

[0025] The above scheme, the present invention proposes a heat treatment process for improving the high-temperature durability of GH2909 alloy, which can solve the technical problems in the prior art such as poor high-temperature durability of GH2909 alloy, complex process, time-consuming process, irregular high-temperature plasticity change, etc.

[0026] The present invention replaces processes such as two solution treatments and two aging treatments, preliminary heat treatment + two-stage solution treatment by one solution treatment + stabilization treatment + one aging treatment, thereby shortening the process flow, reducing the process cost and improving the process efficiency.

[0027] The heat treatment of the present invention adopts stabilization treatment + one-time aging process, which replaces the relatively longer double aging process in the case of the same two-step process. By setting the stabilization treatment in the solid solution and aging temperature range, the G phase precipitates at the alloy grain boundary at this stage, and together with the fine Laves phase at the grain boundary, plays the role of pinning the grain boundary. In addition, the heat treatment process also ensures that the γ′ phase in the alloy matrix is ​​densely precipitated, and the size is small and does not grow excessively. After the heat treatment, there is an appropriate amount of G phase at the grain boundary to strengthen the grain boundary, and the density of the γ′ phase distribution inside the grain is improved. Under the premise of ensuring the strength of the alloy, it has an unexpected effect in improving the high-temperature durability of the alloy.

[0028] The test results of multiple groups of durability performance of the present invention show that compared with the traditional solid solution + double aging process, after being treated by the method of the present invention, the average high-temperature durability life of the alloy can reach more than 90 hours, which is more than 40% higher than before the process optimization.

[0029] In summary, compared with other traditional methods, the method of the present invention performs a uniquely designed efficient heat treatment on the GH2909 alloy through a solid solution treatment + a stabilization treatment + an aging treatment, so that the plasticity and high-temperature durability of the alloy are synergistically improved; the method is simple and easy to operate, green and environmentally friendly, low in cost, short in process, and high in efficiency, which is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is a microstructure diagram of alloy grains and grain boundaries obtained after a heat treatment process for improving the high temperature endurance performance of GH2909 in Example 1 of the present invention;

[0032] Figure 2 This is a microstructure diagram of alloy grains and grain boundaries obtained after the conventional two-solution treatment + double aging heat treatment process in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described below in conjunction with the accompanying drawings.

[0034] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.

[0035] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.

[0036] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.

[0037] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0038] A heat treatment process for improving the high temperature and durability performance of a GH2909 alloy, the heat treatment process for improving the high temperature and durability performance of a GH2909 alloy comprises the following steps:

[0039] S1. Surface pretreatment: pretreating the surface of the GH2909 alloy component to obtain a GH2909 alloy component with a clean surface;

[0040] S2, primary solution treatment: subjecting the GH2909 alloy component whose surface is cleaned in S1 to a primary solution treatment, and air cooling it to room temperature to obtain a GH2909 alloy component after the solution treatment;

[0041] S3, stabilization heat treatment: high temperature pretreatment is performed on the GH2909 alloy component after S2 solid solution treatment, and air cooling is performed to room temperature to obtain a GH2909 alloy component after stabilization treatment;

[0042] S4. Primary aging treatment: Perform primary aging treatment on the GH2909 alloy parts after S3 stabilization heat treatment, air cool to room temperature, and obtain GH2909 alloy with improved high temperature endurance performance.

[0043] In particular, the shape of the GH2909 alloy in S1 is rod-shaped, with sizes of Φ170mm, Φ220mm, and Φ300mm, and the treatment state is standard long-term double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1300-1330MPa, with a standard deviation of 15-27MPa; the yield strength at room temperature is 965-1020MPa, with a standard deviation of 19-35MPa; the elongation at room temperature is 14.7-18.2%, with a standard deviation of 0.7-2.1%; the cross-sectional shrinkage at room temperature is 27-35%, with a standard deviation of 2.7-5.9%; the hardness at room temperature is 370-380HB, with a standard deviation of 2-7HB; the tensile strength at 650℃ is 975-101 0MPa, standard deviation is 15-25MPa; the yield strength at 650℃ high temperature is 827-870MPa, standard deviation is 20-37MPa; the elongation at 650℃ high temperature is 15.5-17.4%, standard deviation is 3.8-7.3%; the cross-sectional shrinkage at 650℃ high temperature is 28.0-43.5%, standard deviation is 6.7-11.9%; the endurance life under 650℃ high temperature and 510MPa stress conditions is 57.7-67.4h, standard deviation is 2.7-7.6h; the elongation after fracture under 650℃ high temperature and 510MPa stress conditions is 12.4-20.8%, standard deviation is 5.1-10.4%; the cross-sectional shrinkage under 650℃ high temperature and 510MPa stress conditions is 29-41%, standard deviation is 4.7-6.9%.

[0044] In particular, the shape of the GH2909 alloy in S1 is annular, with dimensions of 500-600 mm in outer diameter, 400-500 mm in inner diameter, 70-100 mm in height, chord sampling, and the treatment state is standard long-term double aging treatment 1 (720°C×(8±0.5)h / FC→620°C×(8±0.5)h / AC); the room temperature tensile strength is 1300-1340MPa, with a standard deviation of 15-27MPa; the room temperature yield strength is 955-1031MPa, with a standard deviation of 20-37MPa; the room temperature elongation is 15.0-20.2%, with a standard deviation of 0.7-2.3%; the room temperature cross-sectional shrinkage is 27-38%, with a standard deviation of 3.2-4.8%; the room temperature hardness is 365-380HB, with a standard deviation of 2-8HB; the room temperature high temperature resistance is 650°C. The tensile strength is 985-1015MPa, and the standard deviation is 16-19MPa; the yield strength at a high temperature of 650℃ is 837-875MPa, and the standard deviation is 25-37MPa; the elongation at a high temperature of 650℃ is 17.5-20.4%, and the standard deviation is 3.8-6.5%; the cross-sectional shrinkage at a high temperature of 650℃ is 27.0-44.5%, and the standard deviation is 6.7-10.7%; the endurance life under the conditions of a high temperature of 650℃ and a stress of 510MPa is 60-65.4h, and the standard deviation is 2.7-4.6h; the elongation after fracture under the conditions of a high temperature of 650℃ and a stress of 510MPa is 14.4-21.8%, and the standard deviation is 5.1-7.8%; the cross-sectional shrinkage under the conditions of a high temperature of 650℃ and a stress of 510MPa is 31-43%, and the standard deviation is 4.7-5.7%.

[0045] In particular, the shape of the GH2909 alloy in S1 is a square billet with an outer diameter of 100mm×100mm×100mm, and the treatment state is a standard long-time double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC); the room temperature tensile strength is 1310-1345MPa, and the standard deviation is 14-20MPa; the room temperature yield strength is 970-1040MPa, and the standard deviation is 20-40MPa; the room temperature elongation is 15.5-19.2%, and the standard deviation is 0.6-2.4%; the room temperature cross-sectional shrinkage is 26-35%, and the standard deviation is 2.4-4.3%; the room temperature hardness is 375-385HB, and the standard deviation is 3-7HB; the high temperature tensile strength of 650℃ is 980-10 20MPa, standard deviation is 10-18MPa; the yield strength at 650℃ high temperature is 848-877MPa, standard deviation is 25-29MPa; the elongation at 650℃ high temperature is 16.5-21.4%, standard deviation is 3.8-7.1%; the cross-sectional shrinkage at 650℃ high temperature is 27.1-41.8%, standard deviation is 6.7-9.7%; the endurance life under 650℃ high temperature and 510MPa stress conditions is 58.0-66.7h, standard deviation is 1.9-4.1h; the elongation after fracture under 650℃ high temperature and 510MPa stress conditions is 15.1-19.8%, standard deviation is 2.7-6.7%; the cross-sectional shrinkage under 650℃ high temperature and 510MPa stress conditions is 29-42%, standard deviation is 4.8-6.2%.

[0046] In particular, the temperature of the first solution treatment in S2 is 970-1010°C, and the holding time is 60-70min: then air-cooled to room temperature at a rate of 50-80°C / min.

[0047] In particular, the temperature of the stabilization treatment in S3 is 810-840°C, and the holding time is 30-50min: then air-cooled to room temperature, and the air-cooling rate is 50-80°C / min.

[0048] In particular, the temperature of the primary aging treatment in S4 is 640-660°C, and the holding time is 6-8h: then air-cooled to room temperature at a rate of 50-80°C / min.

[0049] In particular, the shape of the GH2909 alloy in S3 is rod-shaped, with sizes of Φ170mm, Φ220mm, and Φ300mm. After a solid solution treatment + stabilization treatment + an aging treatment; the room temperature tensile strength is 1350-1380MPa, with a standard deviation of 10-17MPa; the room temperature yield strength is 1020-1050MPa, with a standard deviation of 9-14MPa; the room temperature elongation is 17.9-23.2%, with a standard deviation of 0.8-1.7%; the room temperature cross-sectional shrinkage is 27-39%, with a standard deviation of 2.9-4.8%; the room temperature hardness is 370-385HB, with a standard deviation of 3-8HB; the high temperature tensile strength of 650℃ is 1005-1025MPa, with a standard deviation of 12-26 MPa; the yield strength at 650℃ is 850-870MPa, with a standard deviation of 14-27MPa; the elongation at 650℃ is 11.5-21.4%, with a standard deviation of 2.3-5.7%; the cross-sectional shrinkage at 650℃ is 35.0-44.5%, with a standard deviation of 2.7-4.9%; the endurance life at 650℃ and 510MPa stress is 90.4-105.1h, with a standard deviation of 2.1-3.4h; the elongation at break at 650℃ and 510MPa stress is 17.1-22.7%, with a standard deviation of 2.7-5.1%; the cross-sectional shrinkage at 650℃ and 510MPa stress is 37.0-47.5%, with a standard deviation of 2.5-5.2%.

[0050] In particular, the shape of the GH2909 alloy in S3 is annular, with dimensions of 500-600mm in outer diameter, 400-500mm in inner diameter, 70-100mm in height, and chordal sampling. After a solid solution treatment + stabilization treatment + an aging treatment, the room temperature tensile strength is 1340-1370MPa, with a standard deviation of 11-15MPa; the room temperature yield strength is 1025-1060MPa, with a standard deviation of 10-14MPa; the room temperature elongation is 18.8-24.5%, with a standard deviation of 0.7-1.4%; the room temperature cross-sectional shrinkage is 30-39%, with a standard deviation of 2.7-4.2%; the room temperature hardness is 370-385HB, with a standard deviation of 3-9HB; the high temperature tensile strength of 650°C is 1000-1020MPa , standard deviation is 12-20MPa; the yield strength at 650℃ high temperature is 830-870MPa, standard deviation is 20-30MPa; the elongation at 650℃ high temperature is 11.5-20.4%, standard deviation is 3.7-5.1%; the cross-sectional shrinkage at 650℃ high temperature is 35.0-41.5%, standard deviation is 2.7-3.8%; the endurance life under 650℃ high temperature and 510MPa stress conditions is 98.4-120.1h, standard deviation is 4.1-6.4h; the elongation after fracture under 650℃ high temperature and 510MPa stress conditions is 18.2-28.7%, standard deviation is 2.2-5.0%; the cross-sectional shrinkage under 650℃ high temperature and 510MPa stress conditions is 38.0-48.0%, standard deviation is 2.3-6.2%.

[0051] In particular, the shape of the GH2909 alloy in S3 is a square billet with an outer diameter of 100mm×100mm×100mm. After a solid solution treatment + stabilization treatment + an aging treatment, the room temperature tensile strength is 1200-1230MPa, with a standard deviation of 15-28MPa; the room temperature yield strength is 890-945MPa, with a standard deviation of 19-35MPa; the room temperature elongation is 14.7-18.2%, with a standard deviation of 0.7-2.1%; the room temperature cross-sectional shrinkage is 26-37%, with a standard deviation of 2.7-5.9%; the room temperature hardness is 360-365HB, with a standard deviation of 2-7HB; the high temperature tensile strength of 650°C is 935-980MPa, with a standard deviation of 15-25MPa ; The yield strength at 650℃ is 784-820MPa, with a standard deviation of 20-40MPa; the elongation at 650℃ is 15.5-29.4%, with a standard deviation of 3.8-9.3%; the cross-sectional shrinkage at 650℃ is 27.0-47.5%, with a standard deviation of 6.7-11.9%; the endurance life at 650℃ and 510MPa stress is 95.4-111.2h, with a standard deviation of 5.1-6.8h; the elongation at break at 650℃ and 510MPa stress is 17.5-24.7%, with a standard deviation of 2.2-4.8%; the cross-sectional shrinkage at 650℃ and 510MPa stress is 36.2-47.1%, with a standard deviation of 2.2-6.9%.

[0052] In particular, the microstructure of GH2909 alloy parts after vacuum brazing + primary aging consists of 73.95-77.45% γ solid solution, 14.71-15.43% γ′ phase, 4.06-5.36% Laves phase, 1.21-1.89% ε phase and 2.57-3.37% G phase; (γ solid solution is generally not studied, and the shape and size are not fixed (Determined) Among them, the shape of the γ′ phase is small spherical or cubic, with an average size of 18.84-19.72nm; the shape of the Laves phase is spherical or short rod-shaped, with an average major axis length of 1.45-1.84μm and an average minor axis length of 0.75-0.86μm; the shape of the ε phase is needle-shaped, with an average length of 0.89-1.61μm; the shape of the G phase is blocky or short rod-shaped, with an average size of 0.91-1.24μm.

[0053] Example 1

[0054] A heat treatment process for improving the high-temperature durability of GH2909 alloy, wherein the GH2909 alloy used is in a rod shape with a size of Φ170, and the composition of each element by mass percentage is: C 0.01%, Si 0.40%, Co 13.48%, Ni 38.06%, Ti 1.64, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the heat treatment process for improving the high-temperature durability of the GH2909 alloy is as follows:

[0055] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ170 mm, and is treated in the standard long-term double aging treatment 1 (720°C×(8±0.5)h / FC→620°C×(8±0.5)h / AC), with a sampling size of Φ10 mm, and the properties are shown in Table 1 below:

[0056] Table 1

[0057]

[0058]

[0059] S2, one solution treatment: the GH2909 alloy component with cleaned surface in S1 is subjected to one solution treatment, the temperature of the one solution treatment is 980°C, and the holding time is 65min; then, it is air-cooled to room temperature at a rate of 65°C / min to obtain the GH2909 alloy component after the solution treatment;

[0060] S3, stabilization treatment: Stabilization treatment is performed on the GH2909 alloy parts after S2 solid solution treatment, the stabilization treatment temperature is 840°C, and the holding time is 30 minutes; then air-cooling to room temperature, the air cooling rate is 65°C / min, and the GH2909 alloy parts after stabilization treatment are obtained;

[0061] S4. Primary aging treatment: The GH2909 alloy parts after stabilization treatment are subjected to primary aging treatment at a temperature of 640°C and a holding time of 6.5h. Thereafter, the parts are air-cooled to room temperature at a rate of 65°C / min to obtain GH2909 alloy parts with improved high temperature durability.

[0062] The GH2909 alloy component of this embodiment is in the shape of a rod, with a size of Φ170 mm and a sampling size of Φ10 mm. After a solid solution treatment + a stabilization treatment + an aging treatment, the performance is shown in Table 2 below:

[0063] Table 2

[0064]

[0065] like Figure 1 As shown in the figure, the microstructure of the GH2909 alloy with improved high temperature durability in this example consists of 76.81% volume fraction of γ solid solution, 14.77% volume fraction of γ′ phase, 4.37% volume fraction of Laves phase, 1.27% volume fraction of ε phase and 2.78% volume fraction of G phase; (γ solid solution is generally not studied, and its shape and size are not fixed) among which, the shape of γ′ phase is small spherical or cubic, with an average size of 18.89nm; the shape of Laves phase is spherical or short rod, with an average major axis length of 1.51μm and an average minor axis length of 0.77μm; the shape of ε phase is needle-shaped, with an average length of 1.12μm; the shape of G phase is blocky or short rod-shaped, with an average size of 0.97μm.

[0066] Comparative Example 1

[0067] A heat treatment process for improving the high-temperature durability of GH2909 alloy, wherein the GH2909 alloy used is in a rod shape with a size of φ170 mm, and the composition of each element by mass percentage is: C 0.01%, Si 0.40%, Co 13.48%, Ni38.06%, Ti 1.64, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the heat treatment process for improving the high-temperature durability of the GH2909 alloy is as follows:

[0068] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ170 mm, and is treated in the standard long-term double aging treatment 1 (720°C×(8±0.5)h / FC→620°C×(8±0.5)h / AC), with a sampling size of Φ10 mm, and the properties are shown in Table 3 below:

[0069] Table 3

[0070]

[0071]

[0072] S2, primary solution treatment: the GH2909 alloy component with cleaned surface in S1 is subjected to a primary solution treatment at a temperature of 990°C and a holding time of 70 min; then air-cooled to room temperature at a rate of 65°C / min to obtain a GH2909 alloy component after the solution treatment;

[0073] S3. Double aging treatment: The GH2909 alloy after S2 solution treatment was subjected to two aging treatments, the aging temperature for the two times was 720°C for 8 hours, then furnace cooled to 620°C for 8 hours; taken out and air cooled to room temperature, the air cooling rate was 65°C / min, and the GH2909 alloy with standard double aging heat treatment 1 was obtained.

[0074] After one solution treatment + two aging treatments, the GH2909 alloy component of this comparative example with a shape of 70mm×50mm×50mm is in a rod shape with a size of Φ170mm and a sampling size of Φ10mm. After the standard solution treatment + double aging treatment, the mechanical properties of the GH2909 alloy are shown in Table 4 below:

[0075] Table 4

[0076]

[0077] like Figure 2 As shown, the structure of the GH2909 alloy of this comparative example 1 is composed of a γ solid solution with a volume fraction of 73.81%, a γ′ phase with a volume fraction of 20.41%, a Laves phase with a volume fraction of 4.48%, an ε phase with a volume fraction of 1.11% and a G phase with a volume fraction of 0.19%; (γ solid solution is generally not studied, and its shape and size are not fixed), wherein the γ′ phase is cubic in shape, with an average size of 29.83 nm; the Laves phase is spherical or short rod-shaped, with an average major axis length of 1.63 μm and an average minor axis length of 0.87 μm; the ε phase is needle-shaped, with an average length of 1.54 μm; the G phase is block-shaped or short rod-shaped, with an average size of 0.59 μm.

[0078] and Figure 1 Compared with the distribution of alloy grains and grain boundary precipitation phases after heat treatment in the embodiment shown in the figure, Figure 2 After the process treatment of Comparative Example 1, the G phase is less distributed at the grain boundary of the alloy, or even no G phase appears.

[0079] From the comparison of the high-temperature endurance life values ​​of Comparative Example 1 and Example 1, it can be seen that the endurance life of the alloy obtained by treating the GH2909 alloy with the process of the present invention can reach 90 hours, which is significantly improved compared with the high-temperature endurance performance after the traditional standard aging treatment, wherein the endurance life is increased by more than 25 hours compared with that before optimization, and the improvement rate exceeds 40%. This solves the technical barrier of low high-temperature endurance performance of the GH2909 alloy in the actual production process.

[0080] Comparative Example 2

[0081] A heat treatment process for improving the high-temperature durability of GH2909 alloy, wherein the GH2909 alloy used is in a rod shape with a size of Φ170, and the composition of each element by mass percentage is: C 0.01%, Si 0.40%, Co 13.48%, Ni 38.06%, Ti 1.64, Nb 4.88%, Al 0.031%, Mo 0.04%, and the balance is Fe and unavoidable impurities; the heat treatment process for improving the high-temperature durability of the GH2909 alloy is as follows:

[0082] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ170 mm, and is treated in the standard long-term double aging treatment 1 (720°C×(8±0.5)h / FC→620°C×(8±0.5)h / AC), with a sampling size of Φ10, and the properties are shown in Table 5 below:

[0083] Table 5

[0084]

[0085] S2, primary solution treatment: the GH2909 alloy component with cleaned surface in S1 is subjected to a primary solution treatment at a temperature of 980°C and a holding time of 65 min; then air-cooled to room temperature at a rate of 65°C / min to obtain a GH2909 alloy component after the primary solution treatment;

[0086] S3, secondary solution treatment: the GH2909 alloy parts after the primary solution treatment in S2 are subjected to secondary solution treatment, the temperature of the secondary solution treatment is 980°C and kept for 65 minutes, then taken out and air-cooled to room temperature, the air-cooling rate is 65°C / min, and the GH2909 alloy parts after the secondary solution treatment are obtained;

[0087] S4. Double aging treatment: The GH2909 alloy parts after the secondary solution treatment in S2 were subjected to two aging treatments. The aging temperature for the two treatments was 720°C for 8 hours, and then the parts were cooled to 620°C with the furnace and kept for 8 hours. The parts were taken out and air-cooled to room temperature at a rate of 65°C / min to obtain the GH2909 alloy parts with standard double aging heat treatment 1.

[0088] The GH2909 alloy component of this comparative example is in the shape of a rod, with a size of Φ170 and a sampling size of Φ10. After two solid solution treatments and double aging treatments, the mechanical properties of the GH2909 alloy are shown in Table 6 below:

[0089] Table 6

[0090]

[0091]

[0092] The microstructure of the GH2909 alloy of this comparative example 2 is composed of a γ solid solution with a volume fraction of 73.81%, a γ′ phase with a volume fraction of 20.16%, a Laves phase with a volume fraction of 4.91%, an ε phase with a volume fraction of 1.06%, and a G phase with a volume fraction of 0.16%. (γ solid solution is generally not studied, and its shape and size are not fixed). Among them, the shape of the γ′ phase is or cubic, with an average size of 29.76nm; the shape of the Laves phase is spherical or short rod-shaped, with an average major axis length of 1.21μm and an average minor axis length of 0.77μm; the shape of the ε phase is needle-shaped, with an average length of 1.40μm; the shape of the G phase is blocky or short rod-shaped, with an average size of 0.55μm

[0093] Comparative Example 1 with Comparative Example 1, Example 1 optimizes the aging treatment method in Comparative Example 1, adopts stabilization treatment to match one low-temperature aging treatment, replaces the standard double aging heat treatment, and shortens the total heat treatment time; Comparative Example 1 with Comparative Example 2, Example 1 optimizes the solid solution and aging heat treatment methods in Comparative Example 2, adopts one solid solution to replace two solid solutions, and adopts stabilization treatment to match one aging treatment to replace the standard double aging treatment. Compared with Comparative Examples 1-2, while optimizing the process, Example 1 precipitates more G phase at the grain boundary of the alloy, and pins the grain boundary together with the fine Laves phase, plays a role in strengthening the grain boundary, thereby improving the plasticity of the material and improving the durability of the alloy at high temperature.

[0094] Under the premise of being in line with actual production, the present invention proposes a heat treatment process suitable for GH2909 alloy, which simplifies the traditional standard aging process. The stabilization treatment is combined with a one-time aging process to improve the durability of the alloy at high temperatures, optimize the process and increase the service life of the alloy.

[0095] Compared with the traditional standard heat treatment process, the heat treatment of the present invention adopts a one-step aging process, which replaces the relatively complex two-step aging process and shortens the aging time. Through stabilization treatment, the G phase precipitates at the alloy grain boundary at this stage, and together with the fine Laves phase at the grain boundary, plays the role of pinning the grain boundary. In addition, the heat treatment process ensures that the γ′ phase in the alloy matrix is ​​densely precipitated, and the size is small and does not grow excessively. After the heat treatment, there is an appropriate amount of G phase at the grain boundary to strengthen the grain boundary, and the density of the γ′ phase distribution inside the grain is improved. Under the premise of ensuring the strength of the alloy, it has an unexpected effect in improving the high-temperature durability of the alloy. The results of multiple groups of durability performance tests show that after being treated with the method described in the present invention, the average high-temperature durability life of the alloy can reach more than 90 hours. Compared with the traditional heat treatment process, the performance improvement is more than 40%.

[0096] Example 2

[0097] A heat treatment process for improving the high temperature and durability performance of a GH2909 alloy. The GH2909 alloy used is in a rod shape with a size of φ220 mm. The composition of each element is recorded by mass percentage as follows: C 0.022%, Si 0.26%, Co 14.08%, Ni 37.66%, Ti 1.67%, Nb 5.09%, Al 0.12%, Mo 0.50%, and the balance is Fe and unavoidable impurities. The heat treatment process for improving the high temperature and durability performance of the GH2909 alloy comprises the following steps:

[0098] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a rod, with a size of Φ220, and the treatment state is a standard long-term double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC), the sampling size is Φ10, and the properties are shown in Table 7 below:

[0099] Table 7

[0100]

[0101]

[0102] S2, a solid solution treatment: the GH2909 alloy component with the cleaned surface of S1 is subjected to a solid solution treatment at a temperature of 1000°C and a holding time of 60 min; then air-cooled to room temperature at a rate of 65°C / min to obtain a GH2909 alloy component after solid solution treatment;

[0103] S3, stabilization treatment: the GH2909 alloy parts after S2 solid solution treatment are stabilized at a temperature of 830°C and a holding time of 35 minutes; then air-cooled to room temperature at a rate of 65°C / min to obtain the GH2909 alloy parts after stabilization treatment;

[0104] S4. Primary aging treatment: The GH2909 alloy parts after S3 solution treatment are subjected to primary aging treatment at a temperature of 640°C and a holding time of 6.5h. Thereafter, the parts are air-cooled to room temperature at a rate of 65°C / min to obtain GH2909 alloy parts with improved high temperature endurance performance.

[0105] The GH2909 alloy component of this embodiment is in the shape of a rod, with a size of Φ220 mm and a sampling size of Φ10 mm. After a solid solution treatment + a stabilization treatment + an aging treatment, the performance is shown in Table 8 below:

[0106] Table 8

[0107]

[0108]

[0109] The microstructure of the GH2909 alloy with improved high-temperature stress-cracking performance in this embodiment consists of a γ solid solution with a volume fraction of 77.19%, a γ′ phase with a volume fraction of 14.34%, a Laves phase with a volume fraction of 4.29%, an ε phase with a volume fraction of 1.21%, and a G phase with a volume fraction of 2.97%. Among them, the γ′ phase is in the shape of a small sphere or a cube with an average size of 18.94 nm; the Laves phase is in the shape of a sphere or a short rod with an average major axis length of 1.61 μm and an average minor axis length of 0.81 μm; the ε phase is in the shape of a needle with an average length of 1.21 μm; the G phase is in the shape of a block or a short rod with an average size of 1.18 μm.

[0110] Example 3

[0111] A heat treatment process for improving the high-temperature durability of a GH2909 alloy. The GH2909 alloy used is in the shape of a ring with an outer diameter of 600 mm, an inner diameter of 500 mm, and a height of 80 mm. The element composition is recorded by mass percentage as follows: C 0.01%, Si 0.38%, Co 13.42%, Ni 37.64%, Ti 1.55%, Nb 4.68%, Al 0.039%, Mo 0.03%, and the balance is Fe and unavoidable impurities. The heat treatment process for improving the high-temperature durability of the GH2909 alloy comprises the following steps:

[0112] S1. Surface pretreatment: The surface of the GH2909 alloy component is pretreated to remove the surface oxide layer or oil stains, and finally cleaned and dried to obtain a GH2909 alloy component with a clean surface; the GH2909 alloy component is in the shape of a ring, with an outer diameter of 600 mm, an inner diameter of 500 mm, and a height of 80 mm. The treatment state is a standard long-term double aging treatment 1 (720°C×(8±0.5)h / FC→620°C×(8±0.5)h / AC), the sampling size is Φ10, and the properties are shown in Table 9 below:

[0113] Table 9

[0114]

[0115]

[0116] S2, a solid solution treatment: the GH2909 alloy component with the cleaned surface of S1 is subjected to a solid solution treatment at a temperature of 1000°C and a holding time of 60 min; then air-cooled to room temperature at a rate of 65°C / min to obtain a GH2909 alloy component after solid solution treatment;

[0117] S3, stabilization treatment: Stabilization treatment is performed on the GH2909 alloy parts after S2 solid solution treatment, the stabilization treatment temperature is 820°C, and the holding time is 40 minutes; then air-cooling to room temperature, the air cooling rate is 65°C / min, and the GH2909 alloy parts after stabilization treatment are obtained;

[0118] S4. Primary aging treatment: The GH2909 alloy after S3 stabilization treatment is subjected to primary aging treatment at a temperature of 645°C and a holding time of 7h. It is then air-cooled to room temperature at a rate of 65°C / min to obtain GH2909 alloy parts with improved high temperature durability.

[0119] The GH2909 alloy component of this embodiment is in the shape of a ring, with an outer diameter of 600 mm, an inner diameter of 500 mm, a height of 80 mm, and a sampling size of Φ10 mm. After a solid solution treatment + a stabilization treatment + an aging treatment, the performance is shown in Table 10 below:

[0120] Table 10

[0121]

[0122]

[0123] The microstructure of the GH2909 alloy with improved high-temperature stress-cracking performance in this embodiment consists of a γ solid solution with a volume fraction of 77.04%, a γ′ phase with a volume fraction of 14.51%, a Laves phase with a volume fraction of 4.57%, an ε phase with a volume fraction of 1.01%, and a G phase with a volume fraction of 2.87%. Among them, the γ′ phase is in the shape of a small sphere or a cube with an average size of 18.89 nm; the Laves phase is in the shape of a sphere or a short rod with an average major axis length of 1.55 μm and an average minor axis length of 0.82 μm; the ε phase is in the shape of a needle with an average length of 1.19 μm; the G phase is in the shape of a block or a short rod with an average size of 1.27 μm.

[0124] The above scheme, the present invention proposes a heat treatment process for improving the high-temperature durability of GH2909 alloy, which can solve the technical problems in the prior art such as poor high-temperature durability of GH2909 alloy, complex process, time-consuming process, irregular high-temperature plasticity change, etc.

[0125] The present invention replaces processes such as two solution treatments and two aging treatments, preliminary heat treatment + two-stage solution treatment by one solution treatment + stabilization treatment + one aging treatment, thereby shortening the process flow, reducing the process cost and improving the process efficiency.

[0126] The heat treatment of the present invention adopts stabilization treatment + one-time aging process, which replaces the relatively longer double aging process in the case of the same two-step process. By setting the stabilization treatment in the solid solution and aging temperature range, the G phase precipitates at the alloy grain boundary at this stage, and together with the fine Laves phase at the grain boundary, plays the role of pinning the grain boundary. In addition, the heat treatment process also ensures that the γ′ phase in the alloy matrix is ​​densely precipitated, and the size is small and does not grow excessively. After the heat treatment, there is an appropriate amount of G phase at the grain boundary to strengthen the grain boundary, and the density of the γ′ phase distribution inside the grain is improved. Under the premise of ensuring the strength of the alloy, it has an unexpected effect in improving the high-temperature durability of the alloy.

[0127] The test results of multiple groups of durability performance of the present invention show that compared with the traditional solid solution + double aging process, after being treated by the method of the present invention, the average high-temperature durability life of the alloy can reach more than 90 hours, which is more than 40% higher than before the process optimization.

[0128] In summary, compared with other traditional methods, the method of the present invention performs a uniquely designed efficient heat treatment on the GH2909 alloy through a solid solution treatment + a stabilization treatment + an aging treatment, so that the plasticity and high-temperature durability of the alloy are synergistically improved; the method is simple and easy to operate, green and environmentally friendly, low in cost, short in process, and high in efficiency, which is conducive to large-scale industrial production and promotion.

[0129] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.

[0130] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can be represented by: a, b, c, ab, ac, bc, or abc, where a, b, c can be single or multiple.

[0131] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0132] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A heat treatment process for improving the high temperature durability of GH2909 alloy, characterized in that: The heat treatment process for improving the high temperature and durability performance of the GH2909 alloy is as follows: S1. Surface pretreatment: pretreating the surface of the GH2909 alloy component to obtain a GH2909 alloy component with a clean surface; S2, primary solution treatment: subjecting the GH2909 alloy component whose surface is cleaned in S1 to a primary solution treatment, and air cooling it to room temperature to obtain a GH2909 alloy component after the solution treatment; S3, stabilization heat treatment: high temperature pretreatment is performed on the GH2909 alloy component after S2 solid solution treatment, and air cooling is performed to room temperature to obtain a GH2909 alloy component after stabilization treatment; S4. Primary aging treatment: Perform primary aging treatment on the GH2909 alloy parts after S3 stabilization heat treatment, air cool to room temperature, and obtain GH2909 alloy with improved high temperature endurance performance.

2. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 1 is characterized in that: The shape of GH2909 alloy in S1 is rod-shaped, with sizes of Φ170mm, φ220mm, and φ300mm. The treatment state is standard long-term double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1300-1330MPa, with a standard deviation of 15-27MPa; the yield strength at room temperature is 965-1020MPa, with a standard deviation of 19-35MPa; the elongation at room temperature is 14.7-18.2%, with a standard deviation of 0.7-2.1%; the cross-sectional shrinkage at room temperature is 27-35%, with a standard deviation of 2.7-5.9%; the hardness at room temperature is 370-380HB, with a standard deviation of 2-7HB; the tensile strength at 650℃ is 975-1010M Pa, standard deviation is 15-25MPa; the yield strength at 650℃ high temperature is 827-870MPa, standard deviation is 20-37MPa; the elongation at 650℃ high temperature is 15.5-17.4%, standard deviation is 3.8-7.3%; the cross-sectional shrinkage at 650℃ high temperature is 28.0-43.5%, standard deviation is 6.7-11.9%; the endurance life under 650℃ high temperature and 510MPa stress conditions is 57.7-67.4h, standard deviation is 2.7-7.6h; the elongation after fracture under 650℃ high temperature and 510MPa stress conditions is 12.4-20.8%, standard deviation is 5.1-10.4%; the cross-sectional shrinkage under 650℃ high temperature and 510MPa stress conditions is 29-41%, standard deviation is 4.7-6.9%.

3. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 1 is characterized in that: The shape of GH2909 alloy in S1 is ring-shaped, with dimensions of 500-600mm in outer diameter, 400-500mm in inner diameter, and 70-100mm in height. The samples are taken in the chord direction, and the treatment state is standard long-term double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1300-1340MPa, with a standard deviation of 15-27MPa; the yield strength at room temperature is 955-1031MPa, with a standard deviation of 20-37MPa; the elongation at room temperature is 15.0-20.2%, with a standard deviation of 0.7-2.3%; the cross-sectional shrinkage at room temperature is 27-38%, with a standard deviation of 3.2-4.8%; the hardness at room temperature is 365-380HB, with a standard deviation of 2-8HB; the tensile strength at high temperature of 650℃ ... The strength is 985-1015MPa, and the standard deviation is 16-19MPa; the yield strength at 650℃ is 837-875MPa, and the standard deviation is 25-37MPa; the elongation at 650℃ is 17.5-20.4%, and the standard deviation is 3.8-6.5%; the cross-sectional shrinkage at 650℃ is 27.0-44.5%, and the standard deviation is 6.7-10.7%; the endurance life at 650℃ and 510MPa stress conditions is 60-65.4h, and the standard deviation is 2.7-4.6h; the elongation at break at 650℃ and 510MPa stress conditions is 14.4-21.8%, and the standard deviation is 5.1-7.8%; the cross-sectional shrinkage at 650℃ and 510MPa stress conditions is 31-43%, and the standard deviation is 4.7-5.7%.

4. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 1 is characterized in that: The shape of GH2909 alloy in S1 is square billet with the size of outer diameter 100mm×100mm×100mm, and the treatment state is standard long-time double aging treatment 1 (720℃×(8±0.5)h / FC→620℃×(8±0.5)h / AC); the tensile strength at room temperature is 1310-1345MPa, and the standard deviation is 14-20MPa; the yield strength at room temperature is 970-1040MPa, and the standard deviation is 20-40MPa; the elongation at room temperature is 15.5-19.2%, and the standard deviation is 0.6-2.4%; the cross-sectional shrinkage at room temperature is 26-35%, and the standard deviation is 2.4-4.3%; the hardness at room temperature is 375-385HB, and the standard deviation is 3-7HB; the tensile strength at 650℃ is 980-1020 MPa, with a standard deviation of 10-18MPa; the yield strength at 650℃ is 848-877MPa, with a standard deviation of 25-29MPa; the elongation at 650℃ is 16.5-21.4%, with a standard deviation of 3.8-7.1%; the cross-sectional shrinkage at 650℃ is 27.1-41.8%, with a standard deviation of 6.7-9.7%; the endurance life at 650℃ and 510MPa stress conditions is 58.0-66.7h, with a standard deviation of 1.9-4.1h; the elongation at break at 650℃ and 510MPa stress conditions is 15.1-19.8%, with a standard deviation of 2.7-6.7%; the cross-sectional shrinkage at 650℃ and 510MPa stress conditions is 29-42%, with a standard deviation of 4.8-6.2%.

5. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 1 is characterized in that: The temperature of the first solution treatment in S2 is 970-1010°C, and the holding time is 60-70min: then air-cooled to room temperature at a rate of 50-80°C / min.

6. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 1 is characterized in that: The temperature of the stabilization treatment in S3 is 810-840°C, and the holding time is 30-50min: then it is air-cooled to room temperature at a rate of 50-80°C / min.

7. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 1 is characterized in that: The temperature of the primary aging treatment in S4 is 640-660°C, and the holding time is 6-8h: then air-cooled to room temperature at a rate of 50-80°C / min.

8. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 2, characterized in that: The shape of GH2909 alloy in S3 is rod-shaped, with sizes of Φ170mm, Φ220mm, and Φ300mm. After a solid solution treatment + stabilization treatment + an aging treatment; the room temperature tensile strength is 1350-1380MPa, with a standard deviation of 10-17MPa; the room temperature yield strength is 1020-1050MPa, with a standard deviation of 9-14MPa; the room temperature elongation is 17.9-23.2%, with a standard deviation of 0.8-1.7%; the room temperature cross-sectional shrinkage is 27-39%, with a standard deviation of 2.9-4.8%; the room temperature hardness is 370-385HB, with a standard deviation of 3-8HB; the high temperature tensile strength of 650℃ is 1005-1025MPa, with a standard deviation of 12-26MP a; The yield strength at 650℃ is 850-870MPa, with a standard deviation of 14-27MPa; the elongation at 650℃ is 11.5-21.4%, with a standard deviation of 2.3-5.7%; the cross-sectional shrinkage at 650℃ is 35.0-44.5%, with a standard deviation of 2.7-4.9%; the endurance life at 650℃ and 510MPa stress is 90.4-105.1h, with a standard deviation of 2.1-3.4h; the elongation at 650℃ and 510MPa stress is 17.1-22.7%, with a standard deviation of 2.7-5.1%; the cross-sectional shrinkage at 650℃ and 510MPa stress is 37.0-47.5%, with a standard deviation of 2.5-5.2%.

9. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 3 is characterized in that: The shape of GH2909 alloy in S3 is ring-shaped, with dimensions of 500-600mm in outer diameter, 400-500mm in inner diameter, and 70-100mm in height. The chordal sampling is carried out after a solid solution treatment + stabilization treatment + an aging treatment; the room temperature tensile strength is 1340-1370MPa, with a standard deviation of 11-15MPa; the room temperature yield strength is 1025-1060MPa, with a standard deviation of 10-14MPa; the room temperature elongation is 18.8-24.5%, with a standard deviation of 0.7-1.4%; the room temperature cross-sectional shrinkage is 30-39%, with a standard deviation of 2.7-4.2%; the room temperature hardness is 370-385HB, with a standard deviation of 3-9HB; the high temperature tensile strength of 650℃ is 1000-1020MPa, with a standard deviation of The standard deviation is 12-20MPa; the yield strength at 650℃ is 830-870MPa, and the standard deviation is 20-30MPa; the elongation at 650℃ is 11.5-20.4%, and the standard deviation is 3.7-5.1%; the cross-sectional shrinkage at 650℃ is 35.0-41.5%, and the standard deviation is 2.7-3.8%; the endurance life under 650℃ and 510MPa stress conditions is 98.4-120.1h, and the standard deviation is 4.1-6.4h; the elongation after fracture under 650℃ and 510MPa stress conditions is 18.2-28.7%, and the standard deviation is 2.2-5.0%; the cross-sectional shrinkage under 650℃ and 510MPa stress conditions is 38.0-48.0%, and the standard deviation is 2.3-6.2%.

10. The heat treatment process for improving the high temperature durability performance of GH2909 alloy according to claim 4, characterized in that: The shape of GH2909 alloy in S3 is a square billet with an outer diameter of 100mm×100mm×100mm. After a solid solution treatment + stabilization treatment + an aging treatment, the room temperature tensile strength is 1200-1230MPa, with a standard deviation of 15-28MPa; the room temperature yield strength is 890-945MPa, with a standard deviation of 19-35MPa; the room temperature elongation is 14.7-18.2%, with a standard deviation of 0.7-2.1%; the room temperature cross-sectional shrinkage is 26-37%, with a standard deviation of 2.7-5.9%; the room temperature hardness is 360-365HB, with a standard deviation of 2-7HB; the high temperature tensile strength of 650℃ is 935-980MPa, with a standard deviation of 15-25MPa; The yield strength at 50℃ is 784-820MPa, with a standard deviation of 20-40MPa; the elongation at 650℃ is 15.5-29.4%, with a standard deviation of 3.8-9.3%; the cross-sectional shrinkage at 650℃ is 27.0-47.5%, with a standard deviation of 6.7-11.9%; the endurance life at 650℃ and 510MPa stress is 95.4-111.2h, with a standard deviation of 5.1-6.8h; the elongation at break at 650℃ and 510MPa stress is 17.5-24.7%, with a standard deviation of 2.2-4.8%; the cross-sectional shrinkage at 650℃ and 510MPa stress is 36.2-47.1%, with a standard deviation of 2.2-6.9%.

Citation Information

Patent Citations

  • Heat treatment technology for improving high-temperature tensile ductility of Ni-Fe-Cr based deformation high-temperature alloy

    CN106834990A

  • Aging strengthening heat treatment method for nickel-based alloy GH4169

    CN110747417A

  • Heat treatment technology for improving room-temperature strength of nickel-based superalloy

    CN113637929A

  • Heat treatment process capable of prolonging high-temperature endurance life of GH4738 alloy subjected to solution treatment

    CN113684432A

  • Heat treatment process for prolonging fatigue life of GH4738 alloy

    CN113862590A

Cited By

  • Heat treatment process for regulating GH2909 alloy gamma'phase uniformity and improving plasticity

    CN122466380A